2022
DOI: 10.1111/gbi.12518
|View full text |Cite
|
Sign up to set email alerts
|

The deposition and significance of an Ediacaran non‐glacial iron formation

Abstract: Most Neoproterozoic iron formations (NIF) are closely associated with global or nearglobal "Snowball Earth" glaciations. Increasingly, however, studies indicate that some NIFs show no robust evidence of glacial association. Many aspects of non-glacial NIF genesis, including the paleo-environmental setting, Fe(II) source, and oxidation mechanisms, are poorly understood. Here, we present a detailed case study of the Jiapigou NIF, a major non-glacial NIF within a Neoproterozoic volcano-sedimentary sequence in Nor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 116 publications
2
4
0
Order By: Relevance
“…Energy dispersive spectroscopy (EDS) analyses (Fig. 2h) indicate that the apatite grains are carbonate uorapatite [CFA, Ca 5 (PO 4 , CO 3 ) 3 F], which is consistent with previous electron probe micro-analyser (EPMA) studies 24 . Most CFA grains are less than 5 μm in diameter (Figs.…”
Section: Resultssupporting
confidence: 88%
See 3 more Smart Citations
“…Energy dispersive spectroscopy (EDS) analyses (Fig. 2h) indicate that the apatite grains are carbonate uorapatite [CFA, Ca 5 (PO 4 , CO 3 ) 3 F], which is consistent with previous electron probe micro-analyser (EPMA) studies 24 . Most CFA grains are less than 5 μm in diameter (Figs.…”
Section: Resultssupporting
confidence: 88%
“…The above observations suggest that the primary source of P to the North Qilian IFs was due to drawdown in association with Fe minerals. In the North Qilian IFs, the dominance of 'primary' hematite implies a hydrous ferric oxide (e.g., ferrihydrite) precursor that likely precipitated in the water column during the oxidation of upwelling ferruginous waters 23,24 . During this process, co-precipitation and adsorption would have delivered P to the sediment, wherein the early diagenetic transfer of ferrihydrite to more stable hematite (which has a much lower sorptive capacity 34 ) would have released P to the porewaters.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Recently, Xu et al (2015) suggested a formation age between 600 and 580 Ma for the basalts in the Zhulongguan Group. Similar age constraints on the corresponding strata were recently provided by Yang X et al ( , 2023. These results confirm an Ediacaran age for the Zhulongguan Group and overlying units.…”
Section: Qilian Mountains Areasupporting
confidence: 87%